2018
DOI: 10.3389/fpsyg.2018.02519
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Performance on Pro-point and Anti-point Tasks

Abstract: Changes in prefrontal cortex are thought to be responsible for many of the characteristic behavioral changes that are seen during adolescence and late adulthood. Disruption of prefrontal cortex is an early sign for many developmental, neurological, and psychiatric disorders. Goal directed eye movements, such as Anti-saccades, have been shown to have high sensitivity as a gross assessment of prefrontal lobe function. Previous studies on the developmental changes of saccades across age have shown that stimulus-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The study also chose a relatively limited duration (a single season), in part because of the known rapid developmental changes occurring in adolescence. 34 However, for long headers, the half-life for the anti-point task appeared to extend beyond the period studied and thus limited our ability to observe an attenuation of the effect of long headers and estimate their true half-life. Future work should explore designs with longer durations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study also chose a relatively limited duration (a single season), in part because of the known rapid developmental changes occurring in adolescence. 34 However, for long headers, the half-life for the anti-point task appeared to extend beyond the period studied and thus limited our ability to observe an attenuation of the effect of long headers and estimate their true half-life. Future work should explore designs with longer durations.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to these main parameters of interest, the model also estimates the effect of additional time-related factors of testing, including control for the number of previous sessions (to control for practice effects), days since the first session (to control for developmental changes 34 ), days since the previous session (to control for any carryover effects), and age of the athletes. Model description and a detailed explanation of the construction of covariates and parameters are provided in Supplementary Appendix A .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies on healthy aging humans have shown that aging affects controlled and conscious processing that impairs goal‐directed ability (de Wit et al., 2014 ; Span et al., 2004 ; Tomás et al., 2016 ; Worthy et al., 2011 ). Elijah used novel tablet‐based pointing tasks to prove the greater effect of age on response time in goal‐directed tasks compared with that in habitual tasks (Li et al., 2018 ). However, aging and atherosclerosis studies showed that atherosclerosis is a marker of cellular senescence (Wang & Bennett, 2012 ).…”
mentioning
confidence: 99%